Molecular Expression Profile of Changes in Rat Acute Spinal Cord Injury - Wang, Jun-Juan; Ye, Guo; Ren, Hao; An, Cheng-Rui; Huang, Lvxing; Chen, Hengyi; Zhang, Hui; Lin, Jun-Xin; Shen, Xilin; Heng, Boon Chin; Zhou, Jing (Frontiers in Cellular Neuroscience, 2021)
Abstract Background: Spinal cord injury (SCI) is a highly lethal and debilitating disease with a variety of etiologies. To date, there is no effective therapeutic modality for a complete cure. The pathological mechanisms of spinal cord injury at the molecular gene and protein expression levels remain unclear. Methods: This study used single-cell transcriptomic analysis and protein microarray analysis to analyzes changes in the gene expression profiles of cells and secretion of inflammatory factors respectively, around the lesion site in a rat SCI model. Results: Single-cell transcriptomic analysis found that three types of glial cells (microglia, astrocyte, oligodendrocyte) becomes activated after acute injury, with GO exhibiting a variety of inflammatory-related terms after injury, such as metabolic processes, immune regulation, and antigen presentation. Protein microarray results showed that the levels of four inflammatory cytokines favoring SCI repair decreased while the levels of nine inflammatory cytokines hindering SCI repair increased after injury. Conclusions: These findings thus reveal the changes in cellular state from homeostatic to reactive cell type after SCI, which contribute to understand the pathology process of SCI, and the potential relationship between glial cells and inflammatory factors after SCI, and provides new theoretical foundation for further elucidating the molecular mechanisms of secondary SCI.